The Production and Investigation of Starch Based Slow Released Encapsulating Agents (Hungarian Journal of Industry and Chemistry, 2010)
Nowadays the protection of environmentally aware has important part in the agriculture. The growth of the plants need fill the gap of soil’s nutrient. His manner included for this the fertilizing. The most developed fertilizers contain the essential microelements (B, Mn, Zn, Cu, Co, Mo), which are needed for plants, and provide their slow releasing. The native starch is a natural biopolymer that can be gained from renewable raw materials. Its good property is that the native starch able to slow the releasing of the micro components. This effect can be improved if the starch gets ionic functional groups that are able to bind cations. Different starch-phosphates were produced in solid-phase modification with changing the conditions, than we investigated the quality of these starch-phosphates (molecular weight distribution, charge density, solubility). We added copper and zinc microelements to these products using ion exchange method, and examined the dissolution of the micro components. In this paper we present our experiences about dissolution of the zinc and copper in different pH.
Keywords: slow release; encapsulating agent; starch derivatives